Evidence from data searches and life-table analyses for gender-related differences in absolute risk of hip fracture after Colles' or spine fracture: Colles' fracture as an early and sensitive marker of skeletal fragility in white men. - Haentjens, P; Johnell, O; Kanis, J; Bouillon, R; Cooper, C; Lamraski, G; Vanderschueren, D; Kaufman, J; Boonen, S (2004)
UNLABELLED: Based on data searches and life-table analyses, we determined the long-term (remaining lifetime) and short-term (10- and 5-year) absolute risks of hip fracture after sustaining a Colles' or spine fracture and searched for potential gender-related differences. In aging men, Colles' fractures carry a higher absolute risk for hip fracture than spinal fractures in contrast to women. These findings support the concept that forearm fracture is an early and sensitive marker of male skeletal fragility. INTRODUCTION: Colles' fracture occurrence has been largely ignored in public health approaches to identify target populations at risk for hip fracture. The aim of this study was to estimate the long-term and short-term absolute risks of hip fracture after sustaining a Colles' or spine fracture and to search for potential gender-related differences in the relationship between fracture history and future fracture risk. MATERIALS AND METHODS: To determine the long-term (remaining lifetime) and short-term (10- and 5-year) absolute risks of hip fracture, we applied life-table methods using U.S. age- and sex-specific hip fracture incidence rates, U.S. age-specific mortality rates for white women and men, pooled hazard ratios for mortality after Colles' and spine fracture, and pooled relative risks for hip fracture after Colles' and spine fracture, estimated from cohort studies by standard meta-analytic methods. RESULTS: Our results indicate that the estimated remaining lifetime risks are dependent on age in both genders. In women, remaining lifetime risks increase until the age of 80 years, when they start to decline because of the competing probabilities of fracture and death. The same pattern is found in men until the age of 85 years, the increment in lifetime risk being even more pronounced. As expected, the risk of sustaining a hip fracture was found to be higher in postmenopausal women with a previous spine fracture compared with those with a history of Colles' fracture. In men, on the other hand, the prospective association between fracture history and subsequent hip fracture risk seemed to be strongest for Colles' fracture. At the age of 50, for example, the remaining lifetime risk was 13% in women with a previous Colles' fracture compared with 15% in the context of a previous spine fracture and 9% among women of the general population. In men at the age of 50 years, the corresponding risk estimates were 8%, 6%, and 3%, respectively. Similar trends were observed when calculating 5- and 10-year risks. CONCLUSIONS: In aging men, Colles' fractures carry a higher absolute risk for hip fracture than spinal fractures in contrast to women. These findings support the concept that forearm fracture is an early and sensitive marker of male skeletal fragility. The gender-related differences reported in this analysis should be taken into account when designing screening and treatment strategies for prevention of hip fracture in men.